Examination of Perceived Norms and Masculinity Threat as Predictors of College Men's Behavioral Intentions as Bystanders in a Party Gang Rape Situation - Darnell, Doyanne A. (2010)
Sexual assault of women is a well-documented phenomenon in U.S. samples, particularly on college campuses. Innovative approaches to prevention encourage men and women to intervene as bystanders in sexual assault situations; however, bystander behavior is notoriously inhibited by various situational factors. This study used a mixed-method approach to better understand the role of situational factors in college men’s bystander behavioral intentions in a party gang rape situation. The first aim was to develop an experimental paradigm using vignette methodology to manipulate the amount of masculinity threat present in a party gang rape situation, which could then be used to explore the effect of masculinity threat on men’s bystander behavioral intentions. Although I was unable to heighten masculinity threat, findings indicate that a previous relationship with the offenders results in men expecting a typical male college bystander to experience less negative affect in the situation. The second aim was to use the vignettes to examine whether men’s perception of the rape-supportive and traditional masculine gender role norms among the offenders involved, as well as indicators of masculinity threat, would predict men’s bystander behavioral intentions. Boding well for bystander intervention programs, the majority (98%) of men reported intention to intervene to stop the assault to some degree, although this intention was lower for men who perceived the party gang rape situation to result in more negative affect for a typical college male bystander. Data depicts the party gang rape situation as one in which masculine norms and masculinity threat are salient; however, these aspects did not play a role in intentions to intervene. Eighteen percent of men reported some intention to join in the assault, which was predicted by perceived masculine norms and men’s demographic characteristics. Findings point to the importance of culturally competent programming and the utility of incorporating a social norms approach in bystander intervention programs. Programs may benefit from addressing concerns about retaliation, particularly as a function of men’s relationships to the offenders. A limitation is the exclusion of individual difference variables to explore whether men’s own attitudes interact with situational factors to predict bystander behavioral intentions